2017
DOI: 10.18203/2320-6012.ijrms20174158
|View full text |Cite
|
Sign up to set email alerts
|

Effect of soaking and sprouting on protein content and transaminase activity in pulses

Abstract: Background: Pulses belong to the family leguminosae. Pulses provide protein and fibre, as well as vitamins and minerals, such as iron, zinc, folate, and magnesium. In addition, the phytochemicals, saponins, and tannins found in pulses possess antioxidant and anti-carcinogenic effects, indicating that pulses may have significant anti-cancer effects. It is the practice of germinating seeds to be eaten raw or cooked. Sprouts can be germinated at home or produced industrially. The metabolic activity of resting see… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 2 publications
0
10
0
1
Order By: Relevance
“…Protein content seems to progressively increase from soaking to germination [ 56 ]. For instance, Dipnaik and Bathere [ 97 ], found a sequential increase in the protein content of legume seeds soaked for 12 h and then sprouted (from 30 ± 1.07% to 32 ± 0.57%, then to 40 ± 0.57% and from 32 ± 1.8% to 40 ± 1.0%, then to 48 ± 0.57% for cowpea and chickpea control, soaked and germinated seeds, respectively). The authors reported that the measured transaminase activity, as an indicator of new protein synthesis, increased in accordance with the increases in seed protein contents [ 97 ].…”
Section: Effects Of Traditional Processing Technologies On Protein St...mentioning
confidence: 99%
“…Protein content seems to progressively increase from soaking to germination [ 56 ]. For instance, Dipnaik and Bathere [ 97 ], found a sequential increase in the protein content of legume seeds soaked for 12 h and then sprouted (from 30 ± 1.07% to 32 ± 0.57%, then to 40 ± 0.57% and from 32 ± 1.8% to 40 ± 1.0%, then to 48 ± 0.57% for cowpea and chickpea control, soaked and germinated seeds, respectively). The authors reported that the measured transaminase activity, as an indicator of new protein synthesis, increased in accordance with the increases in seed protein contents [ 97 ].…”
Section: Effects Of Traditional Processing Technologies On Protein St...mentioning
confidence: 99%
“…Several studies have shown that sprouting increases the protein content of lupin, peas, chickpea, moth beans, soya beans, and mung beans [32,34,35,40,94,[154][155][156]. Researchers have also observed lower protein content in sprouted legumes, resulting from seed types and conditions of sprouting [34,35,157,158]. The change in protein content has been attributed to the interaction between protein degradation and biosynthesis as steeping and germination times increase [33,149,159,160].…”
Section: Effect Of Steeping and Sprouting Time On The Protein Content...mentioning
confidence: 99%
“…The sample without any treatment was considered as control (C). A 12 h soaking period was considered as standard pretreatment time for grains (Dipnaik and Bathere 2017) [5] . By taking this in consideration the total treatment time was fixed as 12 hours.…”
Section: Sample Preparation and Treatmentsmentioning
confidence: 99%